EVALUASI PENGGUNAAN INSTRUMEN SUPERVISI KEPEGAWAIAN DALAM MENINGKATKAN KINERJA ORGANISASI: TINJAUAN LITERATUR - Ummah, Adisty Akhoma; Agraini, T. Rahmilia; Sari, Putri Mayang; Yuliana, Yuliana; Simatupang, Wakhinuddin; Astuti, Murni (Ensiklopedia of Journal, 2025)
Abstract: Staffing supervision is crucial in human resource management to improve organizational performance. This article evaluates the effectiveness of using personnel supervision instruments through a literature review. Supervision instruments, such as performance appraisal forms, interviews, and direct observations, have been proven to provide objective information about employee performance and support appropriate decision-making. This study shows that systematic supervision improves employee motivation and performance and creates deep job satisfaction. However, implementing supervision faces challenges such as a lack of supervisor training, employee resistance, and limited resources. With this analysis, the article recommends improving supervisor training, supporting organizational policies, and integrating technology into the supervision process. This strategy is expected to maximize the positive impact of supervision on individual and organizational performance.Keywords: personnel supervision, organizational performance, supervision instruments, human resource management, job satisfaction.